Plasma glucose level in elective surgical patients administered with 5% dextrose in 0.45% NaCl in comparison with those receiving lactated Ringer's solution - Ananchanok Saringcarinkul (2018)
Objective: To determine the effect of dextrose containing solution (5% dextrose in 0.45% NaCl) compared to non- dextrose containing solution (lactated Ringer's solution) on plasma glucose level in elective surgical patients. Material and Method: A prospective randomized double-blind control trial was conducted on 60 patients aged 18-60, with ASA physical status I to II, who were scheduled for elective surgery at Maharaj Nakorn Chiang Mai Hospital, Thailand between October, 2007 and September, 2008. The patients received either lactated Ringer's solution (Group L), or 5% dextrose in 0.45% NaCl (Group D) in the morning of the operation day. Blood glucose levels were determined before intravenous fluid administration (T0), at the beginning (T 1), after the 1st hr (T2), and at the end of surgery (T3). Results: Mean duration of preoperative fast was almost 11 hrs in both groups; however, none of the patients had preoperative hypoglycemia. The blood sugar levels were significantly higher in the patients receiving 5% dextrose solution compared to the patients receiving lactated Ringer's solution at the beginning, after the 1st hr and at the end of surgery (p-value = 0.06, 0.018 and 0.036 respectively). There were some patients having hyperglycemia after receiving 5% dextrose in 0.45% NaCl during surgery. However, none of the average plasma glucose values in either group was considered as hyperglycemia. Conclusion: Though they fasted many hours before surgery, no patients were found to have hypoglycemia. The large volume of lactate Ringer's solution had minimal effect on the blood sugar levels compared to the levels in 5% dextrose in 0.45% NaCl group. Therefore, lactate Ringer's solution is probably the alternative choice of intravenous fluid for perioperative maintenance and can be used as replacement in healthy patients undergoing elective surgery.